Online sonification improves cycling performance through kinematic and muscular reorganisations - O`Brien, B.; Hardouin, R.; Rao, G.; Bertin, D.; Bourdin, C. (Scientific Reports, 2020)
Based on a previous study that demonstrated the beneficial effects of sonification on cycling performance, this study investigated which kinematic and muscular activities were changed to pedal effectively. An online error-based sonification strategy was developed, such that, when negative torque was applied to the pedal, a squeak sound was produced in real-time in the corresponding headphone. Participants completed four 6-min cycling trials with resistance values associated with their first ventilatory threshold. Different auditory display conditions were used for each trial (Silent, Right, Left, Stereo), where sonification was only presented for 20 s at the start of minutes 1, 2, 3, and 4. Joint kinematics and right leg muscular activities of 10 muscles were simultaneously recorded. Our results showed participants were more effective at pedalling when presented sonification, which was consistent with previously reported findings. In comparison to the Silent condition, sonification significantly limited ankle and knee joint ranges of motion and reduced muscular activations. These findings suggest performance-based sonification significantly affected participants to reduce the complexity of the task by altering the coordination of the degrees of freedom. By making these significant changes to their patterns, participants improved their cycling performance despite lowering joint ranges of motion and muscular activations.